(NzAIRA(B. (NsEWILXSKIJ CIR@LXNIK(B. (NbEZUMNYJ DENX(B:s (NpXESYs - (NwOLXTER m(B. (Nf(B.s ((NmARI fRANSUA(B)s; (NbOMAR[E p(B. (Nos ((NpXER oG@STEN(B)s; (NaRTAMONOW s(B. (Nd(B.s; (N{ENGELI g(B.s; (Nl@BIMOW n(B.s ((NmOSKWA(B:s (NpROSWE]ENIE(B,s, 1987)
(Nw KNIGE(B, (NPREDNAZNA^ENNOJ DLQ WNEKLASSNOGO ^TENIQ STAR[EKLASSNIKOW(B, (NPREDSTAWLENY WYDA@]IESQ PROIZWEDENIQ FRANCUZSKOGO TEATRA \POHI pROSWE]ENIQ (BXVIII (NWEKA(B: (NTRAGEDIQ wOLXTERA (B"(NzAIRA(B" (NI KOMEDII bOMAR[E (B"(NsEWILXSKIJ CIR@LXNIK(B" (NI (B"(NvENITXBA fIGARO(B". (NtEKSTY SNABVENY PREDISLOWIQMI I KOMMENTARIQMI(B.s
(NwOLXTER m(B. (Nf(B. (NzAIRA(B; (NbOMAR[E p(B. (No(B. (NsEWILXSKIJ CIR@LXNIK(B, (NILI t]ETNAQ PREDOSTOROVNOSTX(B. (NbEZUMNYJ DENX(B, (NILI vENITXBA fIGAROs
(NiNW(B.: 260779s
Keywords: (NT]ETNAQ PREDOSTOROVNOSTXs -- (NVENITXBA fIGAROs -- (NTRAGEDIQs -- (NKOMEDIQs -- (NTEATRs